Protective Effect of Grape (Vitis vinifera) Seed Powder and Zinc-Glycine Complex on Growth Traits and Gut Health of Broilers Following Eimeria tenella Challenge - Naila Chand; Pervez Ali; Ibrahim A. Alhidary; Mutassim A. Abdelrahman; Hani Albadani; Murad Ali Khan; Alireza Seidavi; Vito Laudadio; Vincenzo Tufarelli; Rifat Ullah Khan (MDPI AG, 2021)
The current study was conducted to evaluate the impact of grape (Vitis vinifera) seed powder and zinc-glycine complex on growth parameters and cecal health of broiler following Eimeria tenella challenge. A total of 250 day-old male broilers (Hubbard) were distributed into five treatments as follows: I-negative control (basal diet); II-positive control (E. tenella challenge); III-group infected + Amprolium; IV-group coccidial infection + organic zinc (OZ) at 50 ppm + grape seed powder (GSP) at 2.5 g/kg; V-coccidial infection + organic zinc (OZ) at 50 ppm + grape seed powder (GSP) at 5.0 g/kg. From findings, a lower (p < 0.05) feed intake was noted for positive control compared to the other treatment groups. Conversely, higher (p < 0.05) body weight, dressing percentage, and feed conversion ratio were observed in infected + Amprolium, GSP2.5 + OZ50, and GSP5 + OZ50 treatments in comparison to the positive control. Moreover, the positive control showed severe cecal lesions of thickness and hemorrhages with mild congestion. The lesion scores decreased (p < 0.05) in GSP and OZ treated groups compared to the positive control. Significant (p < 0.05) lower oocyst per gram of feces was found in infected + Amprolium, GSP2.5 + OZ50, and GSP5 + OZ50 in comparison to positive control. Supplementing diet with GSP and OZ at both levels showed restoration of intense sloughing of villi. From the present findings, it can be concluded that OZ and grape seed powder positively ameliorated the growth performance, lesion score, and oocysts shedding in broilers infected with E. tenella.